Performance of Phaseolus vulgaris under partial root-zone drying cultivated in a hydrogravitropic system response - Vega Ponce, Emil Cristhian (2017)
In the experimental area of the UNALM (Lima-Perú) was evaluated on partial root-zone drying irrigation treatments (RPR300 and RPR500, ml) and full irrigation (RC300 and RC500, ml control), the impact of xylem potential (Yx) and stomatal conductance (gs) in common bean plants (Phaseolus vulgaris L.) cultivated in systems (pots) of hydrogravitropic response. A randomized complete block design with 12 plants/pots per treatments was used in three replicates. To control the irrigation application and manage to maintain the Yx nonlethal conditions (<-15 bars), a water-soil retention curve was generated. The values of gs before irrigation (between 217.18 and 268.67 mm m-2 s-1) showed that only RPR500 plants were maintained under optimal water conditions, despite low levels of Yx (between -9.92 and -7.33 bar); situation that could be attributed to the ability of the roots to balance those moments when half of these structures were inside soil with low humidity, while the opposite half was favorable soil water level.